The Influence of Competence and Work Environment on the Quality of Public Services Through Motivation at the Investment and One-Stop Integrated Services Office of West Tanjung Jabung Regency - Haviz, M.; Zahari, M.; Akbar, Ali (Dinasti International Journal of Management Science, 2025)
This study aims to determine and analyze the description of work environment competency, motivation and quality of public services at the Investment and One-Stop Integrated Service Office of West Tanjung Jabung Regency and to determine and analyze the influence of competency and work environment on the quality of public services through motivation at the Investment and One-Stop Integrated Service Office of West Tanjung Jabung Regency. This type of research uses descriptive verification research. This study uses the PLS analysis method. Descriptively, competency, work environment, motivation, and quality of public services at the DPMPTSP of West Tanjung Jabung Regency show that competency is in the high category, work environment is in the good category, motivation is in the high category and quality of public services is in the good category. In addition, the results of the study indicate that at the DPMPTSP of West Tanjung Jabung Regency, competency and work environment have a positive and significant influence on motivation and quality of public services, both directly and through the role of motivation as an intervening variable. Increasing employee competency encourages increased work motivation which ultimately has an impact on better quality of public services. Likewise, a conducive work environment can spur employee work enthusiasm so that the quality of public services increases. Self-motivation has been shown to be an important factor that strengthens the relationship between competence, work environment, and the quality of public services.